BEHAVIORAL RELATIONSHIPS MAINTENANCE OF REPRODUCTIVE HEALTH AGAINST THE INCIDENCE OF SEXUALLY TRANSMITTED INFECTIONS - Irwan Irwan; Putri Ayuningtias Mahdang; Nur Ayini S. Lalu (International Journal of Health Science & Medical Research, 2022)
Background: Sexually Transmitted Infections (STIs) are infections that are transmitted through sexual intercourse both vaginally, anally, and orally. The formulation of the problem in this study is what factors are related to the behavior of the Male Sex Group (LSL) to the transmission of sexually transmitted infections. Research methods: This study aims to analyze the relationship of reproductive health maintenance behavior to the incidence of Sexually Transmitted Infections, this type of study is analytical and observational with a Cross-Sectional design. The population consisted of the entire LSL group of 148 people; the study sample numbered 30. The data analysis technique uses the Fisher Exact and Kolmogorov Smirnov tests. Research results; showed that there was a relationship between reproductive health knowledge to the transmission of sexually transmitted infections (P=0.007), no relationship between reproductive organ maintenance behavior to early detection of cervical cancer (P=0.586), there was a relationship between risky sexual behavior to the transmission of sexually transmitted infections (p=0.005). Conclusion; Reproductive health maintenance behavior affects the risk of STI transmission in the LSL group.Keywords: Risky Sexual Behavior;  LSL; LMS.